GEOELECTRICAL RESISTIVITY FOR AGRICULTURAL WATER RESOURCES IN BUNGAYYA VILLAGE, SELAYAR ISLANDS REGENCY, SOUTH SULAWESI - Muhajir, Muhajir; Amran, Amran; Malik, Malik (MSJ : Majority Science Journal, 2026)
Water demand for the agricultural sector in island regions continues to increase in line with population growth and land-use intensification (Kodoatie, 1996; Todd & Mays, 2005). One sustainable alternative for water supply is the utilization of groundwater, particularly deep aquifers. This study aims to identify the potential and characteristics of subsurface aquifers using the geoelectrical resistivity method with a Schlumberger configuration in Bungayya Village, Bontomatenne District, Selayar Islands Regency, South Sulawesi Province. Measurements were conducted at a single vertical electrical sounding (VES) point (GL_01) with a maximum current electrode spacing of AB/2 up to 100 m. The inversion results indicate two main subsurface layers: a surface limestone layer with resistivity values ranging from 126 to 1515.1 Ωm at depths of 0–15 m, and a sandstone layer of the Walanae Formation with resistivity values of 10–126 Ωm at depths of 15–70 m. The sandstone layer is interpreted as a deep aquifer capable of storing and transmitting freshwater with sufficient discharge for agricultural irrigation. Based on the interpretation results, groundwater drilling is recommended to a depth of approximately 70 m. The findings demonstrate that the geoelectrical resistivity method is effective as a preliminary approach for groundwater exploration, particularly in areas characterized by carbonate and sedimentary geological conditions (Telford et al., 1990; Loke, 2000).